2018
DOI: 10.1002/slct.201802555
|View full text |Cite
|
Sign up to set email alerts
|

Superior Electrocatalytic Performance of Au‐Pt Graded Nano‐Alloys Towards Alcohol Oxidation Reaction

Abstract: The electro‐oxidation of methanol, ethanol and glycerol on Au100‐xPtx/C (‘x’=7.0‐86) graded nano‐alloy modified glassy carbon electrode was investigated at cyclic voltammetry. Prepared Au77Pt23/C alloy showed highest electrocatalytic activity, with mass activity of 572 mA mg−1 of Pt for methanol oxidation reaction (MOR) and high mass activity of 750 mA mg−1 of Pt for ethanol oxidation reaction (EOR). Au69Pt31/C alloy exhibited higher mass activity of 221 mA mg−1 of Pt for glycerol oxidation reaction (GOR). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…However, Au's high content decreased the electrochemical active surface area (ECSA), probably due to the agglomeration mentioned before. 34 Prabu et al 36 coated the catalyst on a glassy carbon electrode, shown the highest mass activity at a ratio of 31:69 of Pt to Au. However, changes in an increase or decrease in the Au composition will only reduce the mass activity.…”
Section: Development Of Pt-based and Pdbased Catalyst With Gold Metalmentioning
confidence: 99%
“…However, Au's high content decreased the electrochemical active surface area (ECSA), probably due to the agglomeration mentioned before. 34 Prabu et al 36 coated the catalyst on a glassy carbon electrode, shown the highest mass activity at a ratio of 31:69 of Pt to Au. However, changes in an increase or decrease in the Au composition will only reduce the mass activity.…”
Section: Development Of Pt-based and Pdbased Catalyst With Gold Metalmentioning
confidence: 99%
“…Among various direct alcohol fuel cells (DAFC), methanol, ethanol, ethandiol and other alcohols of small molecular mass were extensively tested as fuel in renewable power generators for portable devices [1–3] . Because of the large energy density, small emission of pollutants, convenient transport, facile storage and low temperature of operation, DAFC have been widely studied to find a promising fuel for low‐temperature fuel cells in portable application [4–5] . Compared with other fuels, ethanol exhibits some advantages such as low cost, ease of storage and transport, non‐toxicity, bio‐renewability and environmentally compatible characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Because of the large energy density, small emission of pollutants, convenient transport, facile storage and low temperature of operation, DAFC have been widely studied to find a promising fuel for low-temperature fuel cells in portable application. [4][5] Compared with other fuels, ethanol exhibits some advantages such as low cost, ease of storage and transport, non-toxicity, bio-renewability and environmentally compatible characteristics. Direct ethanol fuel cells (DEFC) have attracted great interest as a most promising sustainable energy application, [6][7][8] but ethanol oxidation reaction (EOR) on Pt surfaces is well known to yield poisonous properties upon the formation of reaction intermediates, and exhibits a selectivity towards CO 2 between 0.5 % and 7.5 % in acid media.…”
Section: Introductionmentioning
confidence: 99%
“…Responding to these challenges a series of cost-effective and less susceptible towards CO ads poisoning catalysts have been developed. Instead of the pure Pt bimetallic systems, containing the second less expensive metal, and thus the lower Pt loading, such as Pt-Ru [6][7][8][9][10][11], Pt-Au [12,13] and Pt-Pd [14][15][16], have been developed. Similarly, Pt alloying with non-noble (transition) metals, such as Co [17,18], Ni [17], Cu [17], Fe [19], Mn [20], Sn [20,21], Zn [20], etc., facilitated further creating of cheaper catalysts.…”
Section: Introductionmentioning
confidence: 99%